Annual external monitoring mission: BRAC Rural Development Programme (RDP) IV and Non Formal Primary Education Programme (NFPE) II - BRAC (© BRAC, 2016)
1. Introduction 2. RDP IV observations and recommendations: Village organisations, Credit and savings, Employment and income generation 4. NFPE II: Progress against targets in the logical framework , Progress against financial indicators Logical framework analysis, Recommendations.